Ignorance is bliss. How parents of preschool children make sense of front-of-package visuals and claims on food. (1st April 2015) - Abrams, Katie M.; Evans, Caitlin; Duff, Brittany R.L.
Highlights: Playful visuals appeal to children but parents associate them with junk food. Health claims, realistic graphics, and natural claims make products seem healthier. Fruit graphics meant to communicate flavors are instead perceived as ingredients. Parents may make unhealthy food choices as a result of front-of-package information. Parents accept misleading front-of-package claims when making quick food decisions. Abstract: With growing scrutiny over how the food industry advertises products aimed toward children and fewer consumers using nutrition facts panels and ingredient lists, the fronts of food packages have become an increasingly important marketing tool to understand. Front-of-package (FOP) visual and verbal claims play a critical role in capturing consumers' attention and helping them choose foods that fit their goals. Due to only possessing emergent literacy skills, preschool children are attuned to FOP visuals while parents are able to use the visuals in combination with verbal claims to make food choices for their children. The purpose of this focus group study was to explore how parents of preschool children make sense of FOP visual and verbal claims on packaged food products that are intended for their children. Thematic analysis revealed that parents associated aspects that most appeal to their preschool children – the characters and other playful visuals – with higher sugar content and artificial ingredients. However, parents were also easily led to believe the product was healthier based on visuals of fruit, more realistic pictures, health claims, cross-branding with healthier foods, and visuals suggesting the product is more natural. While parents recognized that the health claims and some visuals may not truly mean the food is healthier, they agreed that they rarely think beyond their initial impression. The food industry needs better regulatory guidance on how to communicate flavors and ingredients on package fronts in a way that helps consumers – particularly parents wanting to encourage healthy eating habits for their young children – better match their nutrition goals.